ASSESSMENT OF ACHIEVEMENTS OF THE FIRST PHASE OF IMPLEMENTATION OF THE ENERGY STRATEGY INDICATORS - N. Lubimova (Вестник университета)
The first stage of implementation of the "Energy Strategy up to 2030" is finished in 2015. Estimated implementation of the indicator parameters of the first stage (2008-2015g): power consumption, power generation, power inputs, power structure, specific fuel consumption for electricity and heat, the need for fuel. For a number of indicators of the Energy Strategy are not achieved even limits, for some indicators deviations is minimal. In general, the phase assignment is not fulfilled, and it is obvious that the following steps should be adjusted downwards.